CТАН ПРОФЕСІЙНОЇ ПІДГОТОВКИ СТУДЕНТІВ ПЕДАГОГІЧНОГО КОЛЕДЖУ В АСПЕКТІ ЇХ ПРАВОВОГО ВИХОВАННЯ - Коваль, Інна (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розкрито cтан професійної підготовки студентів педагогічного коледжу в аспекті правового виховання на основі аналізу навчальних планів, програм та навчально-методичного забезпечення. Доведено, що студенти педагогічного коледжу оволодівають правовими знаннями під час вивчення дисципліни «Правознавство» у циклі гуманітарних та соціально-економічних дисциплін нормативної части навчального плану. Встановлено, що дидактично-виховний потенціал, закладений у цій дисципліні, використовується недостатньо. В статье раскрыто состояние профессиональной подготовки студентов педагогического колледжа в аспекте правового воспитания на основе анализа учебных планов, программ и учебно-методического обеспечения. Доказано, что студенты педагогического колледжа овладевают правовыми знаниями при изучении дисциплины «Правоведение» в цикле гуманитарных и социально-экономических дисциплин нормативной части учебного плана. Установлено, что дидактически-воспитательный потенциал, заложенный в этой дисциплине, используется недостаточно. The article deals with the state of training of students of pedagogical college in the aspect of legal education based on analysis of curricula, programs and educational support. Students of Preschool Education 5.01010101, 5.01010201 Primary education, Social pedagogy 5.01010601 acquire legal knowledge while learning discipline «Law» in a series of humanitarian and socio-economic disciplines of normative part of the curriculum. Its study allows to understand the basic concepts and the theory of law, the basic provisions of the Constitution of Ukraine, Ukrainian State properties, rights and freedoms. It was proved that students of Teachers College master legal knowledge while learning discipline «Law» in a series of humanitarian and socio-economic disciplines of normative part of the curriculum. It was established that didactic and educational potential inherent in this discipline used enough. Students have gaps in knowledge of the Education Law, the legal status of subjects of educational relations have skills of practical application of legal knowledge and professional legal skills and sufficient legal literacy. These problems are largely due to the fact that the curricula and training programs of future teachers do not take into account the nature and extent of legal knowledge, professional legal skills are not developed requirements for the selection of optimal content of legal disciplines for students of pedagogical colleges. The study found that the process of teaching law adversely affected by such factors: the lack of uniform approach to determining the set of topics that must be read in the course «Law»; insufficient provision of student teaching of; insufficient use of innovative technology in legal education; insufficient use of active methods; insufficient hours allocated to study law. It was proved that the current challenges and the content and organization of educational process in pedagogical college are solved slowly without the necessary logistical support, which of course affects the quality of teacher training. It is not focused on outcomes, new principles and technology education, retains a gap between a pan and a professional, traditional and problematic, extensive and intensive information and developing training; does not provide for the formation of the future teacher of readiness for pedagogical creativity and collaboration with their pupils, their parents and the public. In its basis it is not put the personality of the future specialist it is not detected and it is not formed its legal education.